PEMBELAJARAN INTERDISIPLINER SENI BUDAYA DAN ILMU PENGETAHUAN ALAM MELALUI KARYA P5 KELAS 5 SDN 4 KARANGBENER - Safitri, Rheza; Yunita Amilia Aini Rohmah; Wasis Wijayanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the work of P5 with the theme of creativity and innovation in interdisciplinary learning between cultural arts and natural sciences in grade 5 SDN 4 Karangbener. Education in elementary schools is currently facing the challenge of integrating various subjects to make learning more relevant to everyday life. Through this research, it is expected to increase students' creativity by combining two subjects into project activities. The research method used was descriptive qualitative with a case study approach involving 16 grade 5 students as research subjects. Data were collected through observation, interviews, and documentation. The results showed that interdisciplinary learning of cultural arts through P5 can improve students' understanding of the material while developing creative and collaborative thinking skills. Students are more enthusiastic in participating in learning because of the connection between the two subjects with the context of everyday life. In addition, researchers also found that this method helps overcome the limitations of media and learning resources. Therefore, interdisciplinary learning has the potential to be an innovative approach to improve the quality of learning in elementary schools.